Atypical Clinical Manifestations in Uterine Myoma: A Case of a 46 Year Old Woman with Abortus History - Thamsil, Syalomita Putri; Leslie, Alexa Griffith Jaya; Pramana, Cipta; Hidayat, Fadil (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
Uterine myoma, also known as uterine fibroids or leiomyomas, represents one of the most common benign gynecological tumors worldwide. Recent epidemiological data reveal that in 2019, approximately 9.64 million new cases of uterine myoma were diagnosed globally. The clinical presentation of uterine myoma varies depending on its severity, ranging from completely asymptomatic cases discovered incidentally to severely symptomatic presentations that significantly impair quality of life. Heavy menstrual bleeding represents the most common clinical manifestation across multiple studies. This study underlines the importance of recognizing the signs and symptoms of uterine myoma, especially in asymptomatic and atypical cases in women diagnosed with uterine myoma. A case of uterine myoma came from a 46-year-old woman (P1A1) with atypical clinical manifestations such as acute nausea-vomiting and left lower abdominal pain. There was a palpable suprapubic mass measuring approximately 6x5 cm, immobile, and tenderness in the left inguinal region. The laboratory tests revealed anemia, leucocytosis, descrease kidney function. There was also hematuria, leucocyteuria and bacteriuria in urinary test. USG showed an enlarged uterus with a slightly hyperechoic lesion with fairly clear boundaries, oval in shape, measuring 5.92 x 5.24 x 6.96 cm in the corpus and fundus areas, accompanied by increased intralesional vascularity with Doppler examination. The patient was undergo undergo laparotomy hysterectomy et salpingoophorectomy sinistra.